PENGEMBANGAN CERITA BERGAMBAR BERBASIS LITERASI SAINS PADA SISWA SEKOLAH INDONESIA KUALA LUMPUR (SIKL) MALAYSIA - Arinta Rezty Wijayaningputri; Innany Mukhlishina; Murtyas Galuh Danawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science literacy is a crucial skill in the era of globalization that allows someone to understand and apply science concepts in everyday life. In the Indonesian School of Kuala Lumpur (SIKL) Malaysia. The urgency of this study is to improve students' science literacy is very much needed to support academic achievement and 21st century competencies. One of the effective media to achieve this goal is picture stories. This media is able to attract students' interest while increasing their understanding of science concepts in an interactive and fun way. Therefore, this study emphasizes the importance of developing picture stories based on science literacy of SIKL Malaysia students. The purpose of this study was to develop valid and interesting picture stories based on science literacy. The development model used is ADDIE (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques used interview and questionnaire techniques. The research instruments include interview sheets, validation questionnaires, and student response questionnaires. Data analysis techniques include media validity analysis and media appeal analysis. The picture stories have been validated by material experts and media experts. The results of the validation of material experts obtained 91.6% with valid criteria. Furthermore, the results of the media expert validation obtained 78% with valid criteria with revision. After the revision of the picture story, a second media expert validation was carried out. The results of the media expert validation were 92% with valid criteria. After the validation was completed, the picture story product was implemented on students of the Indonesian School Kuala Lumpur, Malaysia. Based on the student response questionnaire, students obtained 91% with interesting criteria. The development of picture story media based on scientific literacy was declared valid and interesting to be used as learning for students of the Indonesian School Kuala Lumpur, Malaysia.